Structures of the sodium-coupled phosphate importer SLC34A2 reveal a distinct architecture and gating mechanism - Qinyu Zhu; Omar Almakki; Melinda M. Diver (Proceedings of the National Academy of Sciences, 2026)
Dysregulation of inorganic phosphate (Pi) homeostasis contributes to metabolic disease, cancer, pathological calcification, and kidney disease. Systemic phosphate balance is regulated by SLC34 transporters that mediate renal Pi retention (SLC34A1/A3) and intestinal dietary Pi absorption (SLC34A2). SLC34s couple Pi uptake to the symport of sodium (Na + ) down its electrochemical gradient. Mutations or altered expression of SLC34 proteins are linked to disorders such as chronic kidney disease, where hyperphosphatemia is a major complication, and the lung disease pulmonary alveolar microlithiasis, caused by inactivating SLC34A2 mutations. SLC34A2 is also overexpressed in most ovarian and uterine tumors, making it an attractive target for antibody–drug conjugates. We present cryoelectron microscopy structures of SLC34A2 when the transporter is empty, bound to Na + ions only, fully loaded with Na + ions and Pi, and bound to an inhibitor phosphonoformic acid, revealing its distinct architecture, substrate and ion binding sites, the role of Na + , and multiple transporter states. Pi binds at a highly symmetric, membrane-embedded pocket positioned approximately mid-membrane and is coordinated by its signature four residue QSSS repeat motifs. Na + shapes the Pi-binding pocket and drives the transition from the outward-open to occluded state. Integrated with functional analyses, these structures reveal that SLC34 transporters operate through an atypical alternating access cycle defined by coordinated elevator movements of an auxiliary gate domain. This work lays a foundational framework for understanding Pi regulation and opens avenues for therapeutic strategies targeting disorders linked to phosphate imbalance.